2017
DOI: 10.1089/ars.2016.6748
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy Protects Lungs from Radiation-Induced Endothelial Cell Loss by Restoring Superoxide Dismutase 1 Expression

Abstract: Aims: Radiation-induced normal tissue toxicity is closely linked to endothelial cell (EC) damage and dysfunction (acute effects). However, the underlying mechanisms of radiation-induced adverse late effects with respect to the vascular compartment remain elusive, and no causative radioprotective treatment is available to date. Results: The importance of injury to EC for radiation-induced late toxicity in lungs after whole thorax irradiation (WTI) was investigated using a mouse model of radiation-induced pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 88 publications
2
89
0
Order By: Relevance
“…In our hands, adoptively transferred MSC normalized certain aspects of radiation-induced immune deviation in the lung tissue, normalized vascular function, and attenuated radiation-induced pulmonary fibrosis (36, 37). We and others showed that the anti-inflammatory and anti-fibrotic action of MSC is mediated by the inhibition of TNF-a, IL-1alpha, and interleukin 1 receptor antagonist (249, 251), stimulating the secretion of hepatocyte growth factor (HGF) and PGE2 (250, 252) and restoration of the superoxide dismutase 1 expression (37). …”
Section: Therapeutic Approaches For Radiation-induced Pneumopathymentioning
confidence: 63%
See 4 more Smart Citations
“…In our hands, adoptively transferred MSC normalized certain aspects of radiation-induced immune deviation in the lung tissue, normalized vascular function, and attenuated radiation-induced pulmonary fibrosis (36, 37). We and others showed that the anti-inflammatory and anti-fibrotic action of MSC is mediated by the inhibition of TNF-a, IL-1alpha, and interleukin 1 receptor antagonist (249, 251), stimulating the secretion of hepatocyte growth factor (HGF) and PGE2 (250, 252) and restoration of the superoxide dismutase 1 expression (37). …”
Section: Therapeutic Approaches For Radiation-induced Pneumopathymentioning
confidence: 63%
“…Several reports including own studies revealed that MSC show anti-fibrotic and protective effects in the irradiated lung, and current reviews highlight a potential therapeutic benefit of MSC therapy for the treatment of radiation-induced and BLM-induced tissue damage (36, 37, 248, 263). In our hands, adoptively transferred MSC normalized certain aspects of radiation-induced immune deviation in the lung tissue, normalized vascular function, and attenuated radiation-induced pulmonary fibrosis (36, 37).…”
Section: Therapeutic Approaches For Radiation-induced Pneumopathymentioning
confidence: 95%
See 3 more Smart Citations